Time dependent changing of dynamic characteristics of laboratory arch dam model - Altunisik, Ahmet Can; SevIm, Baris; Bayraktar, Alemdar; Adanur, Suleyman; Gunaydin, Murat (KOREAN SOCIETY OF CIVIL ENGINEERS-KSCE, 2015)
This paper investigates the time dependent changing of dynamic characteristics of laboratory arch dam models using ambient vibration test. For this aim, a prototype arch dam-reservoir-foundation model is constructed in laboratory conditions. The first experimental measurement tests are performed after the poured concrete aged for 10 months for some damage scenarios such as undamaged, minor-damaged and severely damaged of dam body in November 2009. To extract the experimental dynamic characteristics such as natural frequencies, mode shapes and damping ratios, a small impact effect is used as a source of ambient vibrations. Experimental measurements tests are repeated using same excitations considering severely damaged conditions with and without reservoir water in February 2014, and the dynamic characteristics are obtained, experimentally. Enhanced Frequency Domain Decomposition Method in the frequency domain is used to extract the experimental dynamic characteristics. At the end of the study, experimentally identified dynamic characteristics are compared with each other and time effects are investigated in detail. Maximum differences between the natural frequencies obtained as 15.36% and 14.38% in the third mode for empty and full reservoir conditions, respectively. It is thought that the increase of the natural frequencies is resulted from gaining of rigidity of the concrete, ageing, temperature and different environmental effects.
Keywords: ambient vibration test; damage scenarios; dynamic characteristics; enhanced frequency domain decomposition method; prototype arch dam-reservoir-foundation model; SEISMIC RESPONSE; AMBIENT; BEHAVIOR; TESTS; Engineering